ANALYZING THE RELIGIOUS VALUES IN A NOVEL ENTITLED HAFALAN SHALAT DELISA BY TERE LIYE - Diyah Zulfa Jauhara; Eka Sari Setianingsih; Moh. Aniq Khairul Basyar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The background of the research problem was that some parents were less concerned with the religious values of their children. Many children did not care about their religious activities such as the lack of interest in memorizing prayers and reciting the Qur'an. The problem in this research was the religious values contained in Tere Liye's novel “Hafalan Shalat Delisa”. The purpose of this research was to reveal and describe the religious values found in Tere Liye's “Hafalan Shalat Delisa” novel. This research was qualitative research using a qualitative descriptive method by describing events, character attitudes, as well as dialogue between characters using note taking techniques. The validity of the data was measured through source triangulation. The results showed that there were several religious values found in